The formative dimensions in the structure of contemporary Iraqi ceramics and their implications On the products of students of the Art Education Department (Al-Academy, 2024)
The research relied on the descriptive analytical method as it is the most appropriate scientific method to achieve the research goal, which is (revealing the formative dimensions in the structure of contemporary Iraqi ceramics and their repercussions on the products of students of the Department of Art Education).The research community consisted of (10) ceramic works by students of the Art Education Department. The researcher selected a purposive sample of (3) ceramic works by students of the Art Education Department. The researcher took the opinions of the arbitrating experts in selecting the sample models.The most important results are:Formative dimension shapes appeared in the form of modified plants and geometric shapes in each of the samples (1, 3) at a rate of 100%.The compositional dimension appeared through color treatment - using the monochromatic color, which dominates the entire composition, such as brown, blue, and clay, and based on the symbolic and expressive dimensions that color carries and represents and symbolizes that it is predicates and several connotations, and this was 80% in all samples.